Change of the chemical and physical properties of heavy oil before and after CO2 treatment. (18th August 2017) - Zheng, Liming; Jing, Cheng; Liu, Jing; Zhang, Lei
ABSTRACT: In order to improve the heavy oil displacement effect by CO2 flooding, the change of the chemical and physical properties of heavy oil before and after CO2 treatment is systematically investigated by indoor simulation experiment. Experimental results show that CO2 treatment can decrease the amount of the saturates but increase that of the aromatics, and yet has little impact on those of resins and asphaltenes. Besides, the corresponding consequence is that there has an increase in the viscosity of the heavy oil and the particle size of the asphaltene micelle, and a decrease in the conductivity of the heavy oil and n-heptane systems and the stability of the asphaltene micelle after CO2 treatment. The conclusions can provide a certain guidance for high-efficiency development of heavy oil reservoir by CO2 flooding.